Effect of myostatin gene silencing on the expression of extracellular matrix formative genes in caprine foetal fibroblast cells - BORAH, BISWAJYOTI; SINGH, A P; SARKHEL, B C (The Indian Journal of Animal Sciences, 2016)
In vitro model for gene silencing using animal cells culture and use of these cells in production of transgenic animal could be an extremely valuable tool to mitigate the meat demand of the world. Myostatin had been identified as negative myogenic regulator that rolled as muscle mass enhancers when silenced. The present experiment was planned to test the effect of four 29-mer anti-MSTN shRNA constructs on silencing of myostatin gene in caprine foetal fibroblast cells and its effect on extracellular matrix formative genes in the caprine foetal fibroblast cells that are necessary for proliferation, differentiation, regulation and development of muscle in caprine. Experiment shows 55.1 to 91.5% of myostatin silencing in caprine foetal fibroblast cells and in myogenic gene expression; decorin shows down-regulation ranged from 78.46 - 89.03%. Whereas, follistatin found up-regulation (417.33 - 156.73%). The Pearson’s correlation analysis revealed that there is negative correlation between myostatin and follistatin genes whereas decorin shows positive correlation. Result suggests that knock down of MSTN could be a promising approach to improve caprine musculatures and to establish important relationship between MSTN and extracellular matrix.